Geoda experimental escénica - Plan parcial red de caminos patrimoniales (2020)
This work aims to determine the behavior of each of the municipalities of the corridor and the scope of these in the study variables, thus determining that the purpose of the master plan will be to strengthen the connection of municipalities with road infrastructure (route 55) based on educational potential improve the economy, culture and heritage existing in the corridor, since it determines that all variables exist without education but education It depends on these. This plan will be conditioned to the characteristic vocation of each municipality, its departmental connections and the ecological infrastructure determined as an edge of the study area. Thus allowing the approach to the municipality of Tunja where the zonal plan will be the aforementioned regional articulation strategy, which will try to provide the municipality with equipment that will help development and approach to new urban determinants to achieve a profit significant in the index of public space per inhabitant in Tunja.